Uganda Gender Strategy: Building equitable climate-resilient African bean and insect sectors - Mugagga, Isaac; Ouya, Frederick; Babirye, Immaculate; Lutomia, Cosmas; Ketema, Dessalegn; Nchanji, Eileen (Bioversity International and International Center for Tropical Agriculture, 2025)
Uganda’s agricultural industry remains the backbone of rural livelihoods, significantly contributing to national food security, poverty alleviation, and employment. However, the sector remains highly vulnerable to climate risks such as prolonged dry spells, unpredictable rainfall, flooding, and frequent pest and disease outbreaks, all of which reduce productivity and increase household vulnerability (Byandaga et al., 2023; World Bank, 2024). These factors interact with underlying structural inequalities, including gender and age-based disparities, shaping how different groups experience and respond to climatic shocks. Women and youth, who provide most of the labour in smallholder farming, face systematic disadvantages related to land tenure, access to production assets, climatic knowledge, and agribusiness opportunities (FAO, 2023; Mukembo et al., 2020). These persistent inequities reflect broader regional patterns of gendered and intergenerational exclusion across sub-Saharan Africa (Agarwal, 2018; IPCC, 2022). Findings from the BRAINS Uganda Baseline Quantitative Gender Analysis indicate the severity of these differences within the beans, fruit tree, and insect value chains. Women contribute more than 70% of labour on bean plots but remain constrained by limited control over land, restricted decision-making power, and reduced access to extension services and digital tools. Men continue to dominate high-value market channels, income decisions, and leadership positions inside producer organizations, while women are disproportionately concentrated in low-value nodes of the value chain. Youth encounter parallel structural challenges, including uncertain land access, restricted start-up financing, and insufficient integration into climate-smart agribusiness ecosystems. These gender and age-specific inequalities impair family adaptation skills and hamper the adoption of Gender Transformative Socio-Technical Innovation Bundles (GTSTIBs), which are fundamental to climate-resilient agricultural transformation. The BRAINS Gender Strategy understands that tackling these gendered and generational hurdles is vital for unlocking Uganda’s climate-resilient agriculture potential. Within the country context, the approach positions gender-transformative action as both a development priority and a fundamental condition for equitable participation in the beans, fruit tree, and insect value chains. This Uganda-specific Gender Strategy contextualises the broader BRAINS gender framework by linking it with national policy commitments, such as the National Gender Policy and the National Climate Change Policy, while rooting its actions in empirical information provided by Uganda’s baseline gender analysis. It provides a framework for building agency, enhancing equitable access to resources, and fostering inclusive decision-making, so ensuring that climate-resilient innovation processes generate advantages for women, men, and youth across Uganda’s agricultural landscape.